Correlation of serum uric acid and hepatic enzymes in premenopausal and postmenopausal women - DR.V.ARUNA,; DR.J.MOHANALAKSHMI,; DR.K.VIJAYAKUMARI, (International Journal of Pharma and Bio Sciences, 2018)
Postmenopausal period is an important transition state for women due to various psychological, physiological and biochemical changes leading to different health hazards like Depression, Cardiovascular disease, Osteoporosis secondary to estrogen deficiency. Hyperuricemia is more commonly found after menopause rather than in reproductive age group(Increased incidence >15%). Alkaline phosphatase is a key enzyme for mineralization and hepatic isoenzyme being a major component, it’s correlation to serum uric acid and other Hepatic enzymes were assessed in the present study in premenopausal and postmenopausal women.50 Premenopausal women(40-50yrs) and73 Postmenopausal women (>50yrs) who were not pregnant/not infertile were included in the study. Serum samples of all the subjects were analysed on fully automated VITROS 250 (Johnson and Johnson)using kits for Urea; Creatinine; Total Bilirubin, Alanine transaminase, Aspartate transaminase, Alkaline phosphatase and Uric acid.60% of the study group (123) were postmenopausal either naturally attained or surgically induced. Mean serum uric acid levels were significantly elevated in postmenopausal women (5.9±2.49mgs/dl) and were 1.3mgs/dl higher in postmenopausal women than in premenopausal women, statistically significant (p< 0.001).We found a weak positive correlation between SUA & Hepatic enzymes (r = 0.237 ; 0.174 and 0.0069 for ALKP, SGOT & SGPT respectively)in postmenopausal women.The mean ALKP values of postmenopausal subjects were significantly high compared to premenopausal (p<0.01) women. One-way ANOVA of means of the analytesin both groups was statistically highly significant (p<0.00001). Serum uric acid & hepatic enzymes should be evaluated for women attending OPD on complaints relating to bones and joints after cessation of menstrual cycles to alleviate impending risk of HTN/CVD/Liver disorders.